Cohort study assessing the impact of COVID-19 on venous leg ulcer management and associated clinical outcomes in clinical practice in the UK. Issue 2 (20th February 2023) - Guest, Julian F; Fuller, Graham W
Abstract : Objective: To assess the impact of the COVID-19 pandemic on venous leg ulcer (VLU) management by the UK's health services and associated outcomes. Design: Retrospective cohort analysis of the electronic records of patients from The Health Improvement Network database. Setting: Clinical practice in primary and secondary care. Participants: A cohort of 1946 patients of whom 1263, 1153 and 733 had a VLU in 2019, 2020 and 2021, respectively. Primary and secondary outcome measures: Clinical outcomes and wound-related healthcare resource use. Results: VLU healing rate in 2020 and 2021 decreased by 16% and 42%, respectively, compared with 2019 and time to heal increased by >85%. An estimated 3% of patients in 2020 and 2021 had a COVID-19 infection. Also, 1% of patients in both years had VLU-related sepsis, 0.1%–0.2% developed gangrene and 0.3% and 0.6% underwent an amputation on part of the foot or lower limb in 2020 and 2021 (of whom 57% had diabetes), respectively. The number of community-based face-to-face clinician visits decreased by >50% in both years and >35% fewer patients were referred to a hospital specialist. In 2020 and 2021, up to 20% of patients were prescribed dressings without compression compared with 5% in 2019. The total number of wound care products prescribed in 2020 and 2021 was >50% less than that prescribed in 2019, possibly due to the decreased frequency of dressing change from a mean of once every 11 days in 2019 to once every 21 days in 2020 and 2021. Conclusions: There was a significant trend towards decreasing care during 2020 and 2021, which was outside the boundaries considered to be good care. This led to poorer outcomes including lower VLU healing rates and increased risk of amputation. Hence, the COVID-19 pandemic appears to have had a deleterious impact on the health of patients with a VLU.